Analisis Peran Bank Sampah Terhadap Pengembangan Ekonomi Masyarakat Desa - Noviansyah, Wahyu; Nuryadi, Muhammad Hendri; Khairiyakh, Refa’ul (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2026)
The problem of waste in villages is not always seen as a threat to the community. However, it needs to be developed into a resource capable of stimulating the village economy. This study aims to analyze the role of waste banks in villages as instruments for waste management and processing, contributing to the development of the village economy. The study used a mixed approach, with qualitative and quantitative data collection. Qualitative data were collected through observations and interviews in Kemiri Village, Kebakkeramat District, Karanganyar Regency. Quantitative data were collected through a survey of 118 villages in Indonesia. Data were analyzed interactively and descriptively to illustrate the role of waste banks in stimulating the village economy and the impact of waste bank management on village income. The results show that waste banks have an impact on the village economy, creating jobs for villagers in the sectors of sorting, transportation, and reducing waste volume. Furthermore, waste processing can also stimulate the creative economy by producing economically valuable products such as planting media and compost. The direct impact of waste banks is their contribution to village income through donations from village-owned enterprise (BUMDes) businesses, as well as the creation of a clean environment and improved public health.